A high performance lithium–selenium battery using a microporous carbon confined selenium cathode and a compatible electrolyte. Issue 19 (2nd May 2017) - Zhou, Jingjing; Yang, Jun; Xu, Zhixin; Zhang, Tao; Chen, Zhenying; Wang, Jiulin
Abstract : Exceptional performances are obtained for a lithium–selenium battery using a nanostructured Se/C cathode material and a compatible LiDFOB/EC-DMC-FEC carbonate electrolyte. Abstract : Rechargeable lithium–selenium (Li–Se) batteries are promising electrochemical systems with higher energy density than traditional Li ion batteries. Nevertheless, the dissolution of high-order lithium selenides and the shuttle effect in electrolytes lead to low Se utilization, inferior capacity and poor cycling performance. This study proposes a combination of nanostructured Se cathode materials and compatible carbonate electrolytes for promoting the performance of Li–Se batteries. Se/MC composite nanoparticles (∼35 nm) with a moderate Se content (≈51.4 wt%) were prepared by embedding Se into a metal–organic framework derived microporous carbon. The resulting Se/MC cathode exhibits significantly high rate capability and cycling stability in LiDFOB/EC-DMC-FEC electrolyte. It delivers a capacity of 511 mA h gSe −1 after 1000 cycles at 5C, with an inappreciable capacity decay of 0.012% per cycle. Even at a very high rate of 20C, a large capacity of 569 mA h gSe −1 can be obtained, corresponding to a decrease of only 5.6% compared to that at 0.5C. The impressive high rate performance is attributed to the co-effect of selenium confined in ultra-small microporous carbon particles and excellent compatibility of the electrolyte with both the Li anode and selenium composite cathode.